2022
DOI: 10.25103/ijbesar.143.01
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Foreign Direct Investment Inflows: Evidence from West Africa

Abstract: Purpose: The study investigates the effect of corruption on FDI inflows to West Africa, and also establishes a threshold level of corruption for the sub-region. Design/Methodology/Approach: Using secondary data for the period 1999-2018, the study adopted a panel Autoregressive Distributed Lag (ARDL) model to carry out regression analysis. However, to ensure results accuracy and validity, a cross section dependence test, panel unit root test and panel cointegration test was carried out. Findings: The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Besides recent studies that have found support for either the “sand the wheels” hypothesis or the “grease the wheels” hypothesis, there are other studies that have found a non-linear corruption–FDI nexus, a corruption threshold effect or ambiguous results (Luu et al , 2019; Zangina and Hassan, 2020; Padmanabhan et al , 2020; Zander, 2021; Bekoe et al , 2021; Qureshi et al , 2021; Krifa-Schneider et al , 2022; Shaari et al , 2022). By gathering information from 131 nations, Luu et al (2019) looked into the effects of corruption on FDI and its two main entry points: greenfield investment (greenfield) and cross-border mergers and acquisitions (M&As).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides recent studies that have found support for either the “sand the wheels” hypothesis or the “grease the wheels” hypothesis, there are other studies that have found a non-linear corruption–FDI nexus, a corruption threshold effect or ambiguous results (Luu et al , 2019; Zangina and Hassan, 2020; Padmanabhan et al , 2020; Zander, 2021; Bekoe et al , 2021; Qureshi et al , 2021; Krifa-Schneider et al , 2022; Shaari et al , 2022). By gathering information from 131 nations, Luu et al (2019) looked into the effects of corruption on FDI and its two main entry points: greenfield investment (greenfield) and cross-border mergers and acquisitions (M&As).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Again, Bekoe et al (2021) examined how corruption affects FDI inflows to West Africa and establish a threshold level of corruption for the sub-region by using secondary data for the years 1999–2018. Regression analysis was performed using a panel autoregressive distributed lag (ARDL) model in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, corruption reduces property rights, a competitive environment, and transparency while increasing costs (Shaari et al, 2022;Al-Sadiq, 2009;Bekoe et al, 2021;Brada et al, 2012;Pupovic, 2012;Kersan-Skabic, 2013;Castro and Nunes, 2013;Quazi, 2014). However, a few studies (Bellos and Subasat, 2011;Helmy, 2013;Lestari et al, 2022) found that corruption had a statistically insignificant effect on FDI inflows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the effect of foreign direct investment on unemployment differs from country to country and therefore results from such studies cannot be used to generalize and therefore the need to conduct a study using Ghana as case study. It is also worthwhile to mention that for the past two decades, Ghana is the second largest recipient of FDI in West Africa after Nigeria (Bekoe and Abdul Rahaman, 2021) and therefore choosing Ghana for this kind of study cannot be underestimated.…”
Section: Review Of Literaturementioning
confidence: 99%